International comparison of the German evidence-based S3-guidelines on the diagnosis and multimodal treatment of early and locally advanced gastric cancer, including adenocarcinoma of the lower esophagus - Moehler, Markus; Baltin, Christoph T.H.; Ebert, Matthias; Fischbach, Wolfgang; Gockel, Ines; Grenacher, Lars; Hölscher, Arnulf H.; Lordick, Florian; Malfertheiner, Peter; Messmann, Helmut; Meyer, Hans Joachim; Palmqvist, Anne; et al. (Gastric Cancer, 2015)
Background: Clinical guidelines are essential in implementing and maintaining nationwide stage-specific diagnostic and therapeutic standards. In 2011, the first German expert consensus guideline defined the evidence for diagnosis and treatment of early and locally advanced esophagogastric cancers. Here, we compare this guideline with other national guidelines as well as current literature. Methods: The German S3-guideline used an approved development process with de novo literature research, international guideline adaptation, or good clinical practice. Other recent evidence-based national guidelines and current references were compared with German recommendations. Results: In the German S3 and other Western guidelines, adenocarcinomas of the esophagogastric junction (AEG) are classified according to formerly defined AEG I–III subgroups due to the high surgical impact. To stage local disease, computed tomography of the chest and abdomen and endosonography are reinforced. In contrast, laparoscopy is optional for staging. Mucosal cancers (T1a) should be endoscopically resected “en-bloc” to allow complete histological evaluation of lateral and basal margins. For locally advanced cancers of the stomach or esophagogastric junction (≥T3N+), preferred treatment is preoperative and postoperative chemotherapy. Preoperative radiochemotherapy is an evidence-based alternative for large AEG type I–II tumors (≥T3N+). Additionally, some experts recommend treating T2 tumors with a similar approach, mainly because pretherapeutic staging is often considered to be unreliable. Conclusions: The German S3 guideline represents an up-to-date European position with regard to diagnosis, staging, and treatment recommendations for patients with locally advanced esophagogastric cancer. Effects of perioperative chemotherapy versus chemoradiotherapy are still to be investigated for adenocarcinoma of the cardia and the lower esophagus.
CRIS-Team Scopus Importer:2025-03-05
Keywords: Diagnosis; Esophageal cancer; Gastric cancer; Guidelines; Perioperative therapy